KAJIAN KRITIS MENGENAI DEFINISI DAN RUANG LINGKUP SALESMANSHIP - Deva Prudensia Setiawan (Universitas Mercu Buana, 2015)
Word of salesmanship is not widely used. This is a relatively new word in the vocabulary of Indonesian people and are not widely used in the English language literature. In addition, there is a tendency of people hesitate to use this word salesmanship. Doubt is due to ambiguities in the definition and scope of the word indicated by the various definitions vary in meaning and scope. Perhaps, too, there are many people who see the meaning of this word is so trivial and narrow in scope because many people who use this word gives the sense in the context of the narrow sense. Thus, this word sounds too sophisticated for ordinary purposes. We need to see and examine with a critical sense of the word and put it in its rightful place and that we needKeywords : Sales, service, salesmenship